Rollover Index for the Diagnosis of Tripped and Untripped Rollovers - Amir Hossein Kazemian; Majid Fooladi; Hossein Darijani (Latin American Journal of Solids and Structures)
Abstract It is necessary to detect danger as soon as possible to avoid rollover of a vehicle in sudden events. Using rollover index in real time can be used for this purpose. The traditional rollover indices currently applying in the vehicles can only detect the untripped rollover due to severe lateral acceleration in vehicles. These indices cannot detect the tripped rollover resulted from vertical external forces in a long direction. There are recently many quantitative studies about the tripped rollover and an index was also introduced to this kind of rollover. In this research, we examined the dynamics of a SUV to improve this index and also presented a new index to detect the both types of rollovers. The precision and accuracy of the new index was evaluated by simulation in industrial software of Carsim. The numerical results of the new developed model were compared with the test results of an automobile at one-eighth scale in equal conditions and inputs. The results are indicative of the better performance of the new model presented in this research.